Yeast as a Model to Unravel New BRCA2 Functions in Cell Metabolism - Costanza, Alessandra; Guaragnella, Nicoletta; Bobba, Antonella; Manzari, Caterina; L’Abbate, Alberto; Lo Giudice, Claudio; Picardi, Ernesto; D’Erchia, Anna Maria; Pesole, Graziano; Giannattasio, Sergio (Frontiers in Oncology, 2022)
Mutations in BRCA2 gene increase the risk for breast cancer and for other cancer types, including pancreatic and prostate cancer. Since its first identification as an oncosupressor in 1995, the best-characterized function of BRCA2 is in the repair of DNA double-strand breaks (DSBs) by homologous recombination. BRCA2 directly interacts with both RAD51 and single-stranded DNA, mediating loading of RAD51 recombinase to sites of single-stranded DNA. In the absence of an efficient homologous recombination pathway, DSBs accumulate resulting in genome instability, thus supporting tumorigenesis. Yet the precise mechanism by which BRCA2 exerts its tumor suppressor function remains unclear. BRCA2 has also been involved in other biological functions including protection of telomere integrity and stalled replication forks, cell cycle progression, transcriptional control and mitophagy. Recently, we and others have reported a role of BRCA2 in modulating cell death programs through a molecular mechanism conserved in yeast and mammals. Here we hypothesize that BRCA2 is a multifunctional protein which exerts specific functions depending on cell stress response pathway. Based on a differential RNA sequencing analysis carried out on yeast cells either growing or undergoing a regulated cell death process, either in the absence or in the presence of BRCA2, we suggest that BRCA2 causes central carbon metabolism reprogramming in response to death stimuli and encourage further investigation on the role of metabolic reprogramming in BRCA2 oncosuppressive function.